Climate, mobility, and food and nutrition security in Vietnam’s Mekong Delta: Insights from Bạc Liêu - Vaselli, Alessandra; Mastrorillo, Marina; Savelli, Adam; Duong, Thanh Thi; Huynh Thi, Tuyen Thanh; Truong, Mai Tuyet; Tuan, Mai Phuong; Tue, Ha Huy (Bioversity International and International Center for Tropical Agriculture, 2025)
This technical report presents the findings of a partnership between the Alliance of Bioversity International and CIAT (The Alliance, a CGIAR research center) and the Vietnam Ministry of Health’s National Institute of Nutrition (NIN) to examine the linkages between climate change, human mobility, and household food and nutrition security (FNS) outcomes in the Mekong Delta. Following the co-development a climate-related mobility survey questionnaire that was added to the 2024 National Nutrition Surveillance (NNS) in Bạc Liêu province, this report provides initial analysis to support research, policy development, and programming strategies in climate-vulnerable, high out-migration areas in southern Vietnam.